The Roles of Information Diffusion on Financial Risk Spreading on Two-Layer Networks - Lin, Min; Duan, Li; Li, Yanjin; Xiao, Qin (Frontiers in Physics, 2022)
The financial risk spread on the financial networks and the information diffusion on the social networks. How the information diffusion affects the financial risk spreading still lacks a mathematical study. This paper proposes a model to describe the coevolution of financial information diffusion and financial risk spreading on a two-layered network. We use a mean-field approach to describe the spreading dynamics and adopt extensive numerical simulations to simulate the dynamics. We find that financial information diffusion can suppress the financial risk generally. Notably, there exists an optimal information diffusion probability at which the financial risk is greatly suppressed. Our results may shed some light on controlling the financial risk spreading dynamics.